Patterns of drug prescribing to promote lactation in breast feeding mothers: รูปแบบการใช้ยากระตุ้นการหลั่งน้ำนม - C, Phithakham; T, Kritsadathan; J, Puakmuangpol; K, Ngenkhamkong; P, Kanjanarat (Biomedical Sciences and Clinical Medicine, 2020)
Objectives To identify patterns of drug prescribing to promote lactation in breastfeeding mothers. Methods A cross-sectional descriptive study was conducted using retrospective data collection from electronic medical records from January – December 2017. Results Of 1,494 mothers who gave birth, 136 received a galactagogue. The prescription rate was 9.10% with all doctors prescribing domperidone. Most of prescriptions indicated use in the hospital and following discharge (52.21%) and almost all mothers (98.55%) were evaluated before being given a prescription and most mothers had breast milk levels of 0 (34.78%) and received at least one intervention to help promote lactation (100%). The majority were prescribed 30 mg of domperidone per day (64.71%). All received domperidone within 10 days after giving birth and the mean day they received domperidone was on day 6. Conclusion The rate of prescribing to promote lactation in breast feeding mothers was 9.10, with all doctors prescribing domperidone. Almost all mothers receiving a galactagogue were evaluated first and received at least one intervention to help promote lactation before being prescribed medication. Domperidone prescriptions were given within 10 days after birth and the mean day that mothers received domperidone was 6.19